2007
DOI: 10.1515/jpem.2007.20.11.1183
|View full text |Cite
|
Sign up to set email alerts
|

A Low Dose Adrenocorticotropin Test (1 μg ACTH) for the Evaluation of Adrenal Function in Children with ß-Thalassemia Receiving Hypertransfusion with Suboptimal Iron-chelating Therapy

Abstract: A cross-sectional study of adrenal function was carried out in 48 patients with beta-thalassemia who were receiving hypertransfusion with suboptimal desferoxamine. A low dose adrenocorticotropic hormone (1 microg ACTH) stimulation test was performed using the cut-off criteria of peak cortisol for adrenal sufficiency >18 microg/dl. Adrenal impairment was diagnosed in 22 patients, giving a prevalence of 45.8%. The peak cortisol concentrations in normal and impaired adrenal function groups were 26.22 +/- 2.84 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…This is relatively high compared with other studies 1,2,4,5,22 , but may be due to a relatively conservative peak cortisol cut-off used (18 μg/dL), as well as a somewhat small study cohort. There have been various proposed cut-off levels to define adrenal insufficiency using the GST in non-thalassemia major populations.…”
Section: Discussionmentioning
confidence: 67%
“…This is relatively high compared with other studies 1,2,4,5,22 , but may be due to a relatively conservative peak cortisol cut-off used (18 μg/dL), as well as a somewhat small study cohort. There have been various proposed cut-off levels to define adrenal insufficiency using the GST in non-thalassemia major populations.…”
Section: Discussionmentioning
confidence: 67%
“…Among the endocrine dysfunctions, hypogonadism, growth retardation and bone demineralization are the most frequent in thalassaemia. As for the pituitary-adrenal axis, previous studies have reported a variable prevalence of impaired function, ranging from 0 to 45.8% depending on the degree of iron overload, but also on the tests used for diagnosis (2)(3)(4)(5)(6)(7). Furthermore, the majority of studies addressing this issue have been performed in children or young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Primary myocardial dysfunction can be caused by hypoparathyroidism [168][169][170] and hypothyroidism, 171,172 and these conditions may exacerbate iron cardiomyopathy. Decreased adrenal reserve is also common in TM, [173][174][175][176][177][178] and patients in HF should be treated as though they have adrenal insufficiency until proven otherwise. Hypogonadotrophic hypogonadism is the most common endocrinopathy observed in TM, 1,179 and low sex steroids may exacerbate HF symptoms.…”
Section: Endocrine Metabolic and Infectious Comorbiditiesmentioning
confidence: 99%
“…Give hydrocortisone on the presumption of inadequate adrenal response to stress. 175 10. Check thyroid, liver, and renal function and calcium, magnesium, vitamin D, carnitine, and other metabolic parameters and correct these when necessary.…”
Section: Management Of Acute Decompensated Hf In Tmmentioning
confidence: 99%